2012
DOI: 10.1177/0300985812469635
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Parelaphostrongylus tenuis–Associated Choriomeningitis in a Guinea Pig With Neurologic Signs

Abstract: An adult male guinea pig (Cavia porcellus) with a 1-month history of hind limb paresis, torticollis, and seizures was euthanized and submitted for necropsy. Gross examination was unremarkable, but histologic examination revealed multifocal eosinophilic and lymphoplasmacytic choriomeningitis and cross sections of nematode parasites within the leptomeninges of the midbrain and diencephalon. Morphologic features of the nematode were consistent with a metastrongyle, and the parasite was identified as Parelaphostro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Future studies utilizing experimental infections are crucial to adequately assess the viability of this specific assay for validation purposes. This would require the adaptation of this assay to non-cervid species and could be applied to a guinea pig model capable of natural infection with the parasite 23 , 24 . An alternative to live-animal experiments could be sera sourced from livestock patients that enter our hospital with known infection status.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies utilizing experimental infections are crucial to adequately assess the viability of this specific assay for validation purposes. This would require the adaptation of this assay to non-cervid species and could be applied to a guinea pig model capable of natural infection with the parasite 23 , 24 . An alternative to live-animal experiments could be sera sourced from livestock patients that enter our hospital with known infection status.…”
Section: Discussionmentioning
confidence: 99%
“…Although its definitive host is the white-tailed deer, a number of studies have confirmed that P. tenuis can parasitize many different hosts, including elk, moose ( Alces alces ), llamas ( Lama glama ), alpacas ( Vicugna pacos ), goats ( Capra hircus ), cattle ( Bos taurus ), horses ( Equus caballus ), bison ( Bison bison ), sika deer ( Cervus nippon ) and guinea pigs ( Cavia porcellus ; Anderson, 1972; Lankester, 2001, 2010; Weiss et al ., 2008; Whitehead and Bedenice, 2009; Gerhold et al ., 2010; Tanabe et al ., 2010; Mitchell et al ., 2011; Southard et al ., 2012; Dobey et al ., 2014; Gerhold and Hickling, 2016). To date, the majority of these studies have focused on genetic confirmation of host infection and identification of morphologically indistinguishable dorsal-spined larvae in Elaphostrongyline species (Gajadhar et al ., 2000; Kutz et al ., 2001; Gerhold et al ., 2010; Dobey et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Nested PCR has been used to confirm the presence of Parelaphostrongylus DNA in fixed nervous tissue, and the presence of P. tenuis and related species have been confirmed with sequencing. 4,11,16,17 Previous reports of Parelaphostrongylus spp. infection in cattle are rare, and only reported in calves < 1 y old.…”
mentioning
confidence: 99%
“…Nested PCR has been used to confirm the presence of Parelaphostrongylus DNA in fixed nervous tissue, and the presence of P. tenuis and related species have been confirmed with sequencing. 4,11,16,17…”
mentioning
confidence: 99%